Role Ambiguity and Work Environment on Turnover Intention With Work Stress As Moderation: Case Study at Bank Rakyat Indonesia (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aims to analyze the effect of role ambiguity and work environment on turnover intention with work stress as moderation. This quantitative research uses a sample of 50 respondents. Data analysis used Moderated Regression Analysis (MRA) with the SPSS program. Based on the results of the analysis it was concluded that (1) role ambiguity has a positive effect on work stress. (2) The work environment has no effect on work stress. (3) Role ambiguity has a significant positive effect on Turnover Intention. (4) Work environment has a significant negative effect on Turnover Intention. (5) Job Stress strengthens the influence of role ambiguity on Turnover Intention and (6) Job stress weakens the influence of the work environment on Turnover Intention. To minimize Turnover Intention, PT. Bank BRI (Persero) Tbk Sinjai Branch Office, must pay attention and clarify the division of labor for employees so that there is no ambiguity in roles in carrying out tasks as well as improving and paying attention to the quality of the employee’s work environment in communication relations between employees. This is aimed at creating and increasing work loyalty for employees and minimizing stress for employees and also reducing turnover rates.